A chiral helical self-assembly for electrochemical recognition of tryptophan enantiomers - Jiapei Yang; Datong Wu; Gao-Chao Fan; Linzheng Ma; Yongxin Tao; Yong Qin; Yong Kong (Electrochemistry Communications, 2019)
Molecular self-assembly has been regarded as a promising strategy for the construction of chiral sensing devices. Here, (1R,2R)-N,N-didodecylcyclohexane-1,2-dicarboxamide (DDC) was synthesized and then self-assembled in alcohol, and a chiral helical structure could be formed owing to the intermolecular hydrogen bond and the polarity effect of solvent. The chirality of the resultant helical self-assembly was confirmed by circular dichroism (CD) spectra, and then the chiral helical self-assembly was used for electrochemical recognition of tryptophan (Trp) enantiomers. Due to the higher affinity of the self-assembly toward L-Trp than D-Trp, which was revealed by hydrophilicity evaluation, efficient recognition of the Trp enantiomers (IL-Trp/ID-Trp = 8.74) was achieved. Keywords: Chirality, Self-assembly, Chiral helical structure, Electrochemical recognition, Tryptophan enantiomers